On the α−ψ-Contractive Mappings in C∗-Algebra Valued b-Metric Spaces and Fixed Point Theorems - Saleh Omran; Ibtisam Masmali (Journal of Mathematics)
In this paper, for a unital C∗-algebra A, we introduce a version of α-ψ-contractive mappings in C∗-algebra valued b-metric spaces, and we prove some Banach fixed point theorems and give some examples to illustrate our results.